Are antibiotic-resistant pathogens more common in subsequent episodes of diabetic foot infection?. (June 2017) - Lebowitz, Dan; Gariani, Karim; Kressmann, Benjamin; Dach, Elodie von; Huttner, Benedikt; Bartolone, Placido; Lê, Nam; Mohamad, Morad; Lipsky, Benjamin A.; Uçkay, Ilker
Summary: Background: After antibiotic therapy of an initial diabetic foot infection (DFI), pathogens isolated from subsequent episodes might become more resistant to commonly prescribed antibiotics. If so, this might require a modification of the current recommendations for the selection of empiric antibiotic therapy. This study investigated whether the Infectious Diseases Society of America (IDSA) DFI guideline recommendations should be modified based on the number of past DFI episodes. Methods: This was a single-centre retrospective cohort survey of DFI patients seen during the years 2010 to 2016. Results: A total 1018 episodes of DFI in 482 adult patients were identified. These patients were followed-up for a median of 3.3 years after the first DFI episode. The total number of episodes was 2257 and the median interval between recurrent episodes was 7.6 months. Among the recurrent DFIs, the causative pathogens were the same as in the previous episode in only 43% of cases (158/365). Staphylococcus aureus was the predominant pathogen in all episodes (range 1 to 13 episodes) and was not more prevalent with the increasing number of episodes. DFIs were treated with systemic antibiotics for a median duration of 20 days (interquartile range 11–35 days). Overall, there was no significant increase in the incidence of antibiotic resistance to methicillin, rifampicin, clindamycin, or ciprofloxacin over the episodes (Pearson's Chi-square test p -values of 0.76, 1.00, 0.06, and 0.46, respectively; corresponding p -values for trend of 0.21, 0.27, 0.38, and 0.08, respectively). Conclusions: After the successful treatment of a DFI, recurrent episodes are frequent. A history of a previous DFI episode did not predict a greater likelihood of any antibiotic-resistant isolate in subsequent episodes. Thus, broadening the spectrum of empiric antibiotic therapy for recurrent episodes of DFI does not appear necessary.